2006
DOI: 10.1128/aem.00132-06
|View full text |Cite
|
Sign up to set email alerts
|

New Lineage of Filamentous, Spore-Forming, Gram-Positive Bacteria from Soil

Abstract: A novel bacterial strain that was isolated from an Italian soil and was designated SOSP1-21 T forms branched mycelia in solid and liquid media and has a filamentous morphology similar to that of some genera belonging to the Actinobacteria. Electron microscopy showed that this organism has a grape-like appearance, resulting from interlacing of spores originating from sporophoric hyphae. Ten strains that are morphologically related to SOSP1-21 T were recovered from soil. Phylogenetic analyses of 16S rRNA gene se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
131
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(139 citation statements)
references
References 48 publications
5
131
0
1
Order By: Relevance
“…Recently, a novel strain was isolated from a soil and named Ktedobacter racemifer (11). The bacterium is a Gram-positive, aerobic, chemolithoorganoheterotrophic organism that produces branched vegetative mycelia, growing well under microaerobic conditions; this finding further expanded the morphological diversity of the phylum.…”
Section: Special Issuementioning
confidence: 90%
See 1 more Smart Citation
“…Recently, a novel strain was isolated from a soil and named Ktedobacter racemifer (11). The bacterium is a Gram-positive, aerobic, chemolithoorganoheterotrophic organism that produces branched vegetative mycelia, growing well under microaerobic conditions; this finding further expanded the morphological diversity of the phylum.…”
Section: Special Issuementioning
confidence: 90%
“…The bacterium is a Gram-positive, aerobic, chemolithoorganoheterotrophic organism that produces branched vegetative mycelia, growing well under microaerobic conditions; this finding further expanded the morphological diversity of the phylum. Phylogenetically, the bacterium represents a new subphylum-level clade of the Chloroflexi phylum, to which the name Ktedonobacteria classis nov. has been given (11,23). The subphylum (class)-level clade contains a variety of environmental gene clones (>100 sequences in public databases) retrieved mainly from soil samples (these sequences can be browsed on the recent version of the greengene database (http://greengenes.lbl.gov/).…”
Section: Special Issuementioning
confidence: 99%
“…The class Ktedonobacteria was first proposed by Cavaletti et al (2006) and later placed in the phylum Chloroflexi (Yabe et al, 2011). The class currently consists of only five species: Ktedonobacter racemifer (Cavaletti et al, 2006) and Thermosporothrix hazakensis (Yabe et al, 2010a) belonging to the order Ktedonobacterales, and Thermogemmatispora onikobensis (Yabe et al, 2011), Thermogemmatispora foliorum (Yabe et al, 2011) and Thermogemmatispora carboxidivorans (King & King, 2014) belonging to the order Thermogemmatisporales.…”
Section: T )mentioning
confidence: 99%
“…These sequences, which are most closely related to a class of bacteria consisting of a majority of thermophiles, have not been observed in Canopy site coxL or 16S rRNA gene sequence libraries. Thus, one could anticipate an adaptive response to elevated temperature for Bare cinder CO uptake even though some Ktedonobacteria are mesophilic (Cavaletti et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Previous molecular ecological analyses have also shown that Bare cinder CO oxidizer communities consist primarily of taxa most closely related to Ktedonobacteria (Weber and King, 2010), a group of largely thermophilic or thermotolerant strains isolated from hot compost and geothermally-heated soils (Cavaletti et al, 2006;Stott et al, 2008;Yabe et al, 2010a, b). The presence of Ktedonobacterialike taxa in Bare cinders is consistent with results from Ranneklev and Bååth (2001), which indicate that fluctuating thermal regimes can select for and maintain thermophilic or thermotolerant communities simultaneously with mesophilic communities.…”
Section: Introductionmentioning
confidence: 99%